Entrepreneurial Intention: Categorization, Classification of Constructs and Proposition of a Model - Fellipe Silva Martins; Eduardo Biagi Almeida Santos; Amélia Silveira (BBR: Brazilian Business Review)
Literature review studies on Entrepreneurial Intention (EI) point to a future of high standardization (Liñán & Fayolle, 2015) and potential impoverishment of the current research (Terjesen, Hessels, & Li, 2013). There is an over-standardization in studies on EI, and a focus on potential dogmatism in the area – that is, theoretical and methodological inflexibility with replication based on alteration only in substantive domain of EI. The objective of this study is to broaden the focus of the literature review on EI. The research design is descriptive, with the use of quantitative data. We adopt the bibliometric technique in the field of research, based on the Principle of Least Effort (Zipf, 1949). We consider the Reinert (1993) method. Four classes emerged in the analysis. The relation between these classes indicated the concern of the studies on EI in replicating methods, techniques and analyses to the new profiles and roles of the entrepreneur. These results enabled the proposition of a preliminary model that increases the future opportunities for studies on EI.